An immersed interface methodology for simulating supersonic spacecraft parachutes with fluid–structure interaction. (October 2022) - Boustani, Jonathan; Barad, Michael F.; Kiris, Cetin C.; Brehm, Christoph
Abstract: The capability of a computational fluid–structure interaction method for simulating thin shell structures with an immersed boundary method and a nonlinear structural dynamics solver is extended in order to simulate supersonic spacecraft parachutes. Methodologies for the representation and motion tracking of thin, sub-grid resolution, thickness Lagrangian geometries in a static Eulerian background mesh are presented in detail. Logical functions for constructing reliable near-wall finite difference operators in the presence of thin geometries and trapped/concave volumes of space are presented. The Darcy–Forchheimer momentum equation is solved as a jump condition at the immersed interface in order to model the porosity of parachute broadcloth. A parallel contact identification and enforcement strategy based on first principles is introduced and validated. The coupled method is then used to simulate wind tunnel experiments conducted to support the Mars Science Laboratory (MSL) mission. In these experiments, a sub-scale MSL disk-gap-band parachute is inflated in a range of Mach numbers and dynamic pressures. The computational method shows good agreement with the experimental data, and where available, other simulation and empirical data, in terms of the opening load magnitude at various Mach numbers and the sustained aerodynamic performance measured by the coefficient of drag. Following quantitative comparison, a qualitative analysis is performed to investigate the effect of freestream Mach number, material porosity, and the bluff upstream payload on the main flow features. Highlights: Expanded the capabilities of an IIM to handle thin, complex, and moving geometries. Developed and validated an IIM jump condition for modeling thin, porous media. Developed and validated a penalty contact formulation derived from first principles. Simulated the inflation of a spacecraft disk-gap-band parachute in supersonic flow. Studied the mechanisms driving the dynamics of supersonic parachute inflation.